2009
DOI: 10.1038/aps.2009.74
|View full text |Cite
|
Sign up to set email alerts
|

Liquiritigenin inhibits Aβ25–35-induced neurotoxicity and secretion of Aβ1–40 in rat hippocampal neurons

Abstract: Aim: To examine whether liquiritigenin, a newly found agonist of selective estrogen receptor-β, has neuroprotective activity against β-amyloid peptide (Aβ) in rat hippocampal neurons. Methods: Primary cultures of rat hippocampal neurons were pretreated with liquiritigenin (0.02, 0.2, and 2 μmol/L) prior to Aβ 25-35 exposure. Following treatment, viability of the cells was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide analysis and by a lactate dehydrogenase activity-based cytotoxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…After 10 d's culture, neurons were exposed to Aβ [25][26][27][28][29][30][31][32][33][34][35] at different concentrations (10,20,30,40 and 50 µM) for 24 h, then MTT assay was used to determine the cell viability. Results showed that Aβ [25][26][27][28][29][30][31][32][33][34][35] insult decreased cell survival in a concentration dependent manner (Fig. 4A), and 30 µM of Aβ [25][26][27][28][29][30][31][32][33][34][35] was the sublethal level, thus was used in the following experiments.…”
Section: Osthole Reduced Intracellular Aβ Levels In Neural Cellsmentioning
confidence: 99%
See 4 more Smart Citations
“…After 10 d's culture, neurons were exposed to Aβ [25][26][27][28][29][30][31][32][33][34][35] at different concentrations (10,20,30,40 and 50 µM) for 24 h, then MTT assay was used to determine the cell viability. Results showed that Aβ [25][26][27][28][29][30][31][32][33][34][35] insult decreased cell survival in a concentration dependent manner (Fig. 4A), and 30 µM of Aβ [25][26][27][28][29][30][31][32][33][34][35] was the sublethal level, thus was used in the following experiments.…”
Section: Osthole Reduced Intracellular Aβ Levels In Neural Cellsmentioning
confidence: 99%
“…Osthole Inhibited Aβ-Induced Synapsin-1 Reduction To further investigate the effect of osthole on synaptic proteins, neurons were pre-treated with osthole (50 µM, 24 h) before Aβ [25][26][27][28][29][30][31][32][33][34][35] exposure, and synapsin-1 expression was measured by immunofluorescence and quantitative analysis. As shown in Figs.…”
Section: Osthole Reduced Intracellular Aβ Levels In Neural Cellsmentioning
confidence: 99%
See 3 more Smart Citations